Curating the City: Begandring Soerabaia and the Production of Public Space - Huwrien'in, Mazma De; Basundoro, Purnawan (JURNAL SOSIAL HUMANIORA (JSH), 2025)
This paper examines the role of the heritage community of Begandring Soerabaia in the production of public space employing Henri Lefebvre's concept of social space as a theoretical framework. Focusing on the "Parade Oud Soerabaja" photography exhibition held at Balai Pemuda Surabaya, the study explores how historical narratives and archival materials are mobilized to generate immersive, socially meaningful experiences. It argues that Begandring’s initiatives—through cultural programming, community gatherings, and dialogic engagement—actively contribute to the transformation of urban heritage spaces into dynamic sites of memory, identity, and civic interaction. The exhibition is situated within Lefebvre's spatial triad, and this study highlights how Balai Pemuda functions as a living space shaped by historical continuity, cultural exchange, and communal agency. Finally, the paper emphasizes the significance of grassroots heritage activism in reconfiguring public spaces and preserving urban cultural memory